Shame-coping in professional soccer players : an exploratory interview analysis - Hofseth, E.; Voktor Pedersen, J.; Jordet, G.; Toering, T. (International Journal of Sport Psychology, 2017)
This study explored, using in-depth interviews, ways in which professional soccer players (N = 6, Mage = 25.33, SD = 4.44) experience and cope with shame following performance failures during matches, and while working on their weaknesses during training. Data was analyzed inductively and deductively using direct and conventional content analysis. Results showed that players were particularly likely to experience shame in response to performance failures during matches. They were found to employ specific problem-focused (learning) and emotionfocused coping strategies ("hiding"). At an intra-personal level, how players coped with shame seemed to have an influence on their performance and skill development.